Evaluation of Hypochromic Microcytic Anemia in Children Presenting in Pediatrics OPD Combined Military Hospital (CMH) Sargodha - Korejo, Saqib hussain; Arif, Adeel; Zahid, Muhammad; Nizamani, Mohsin Hussain; Hussain, Muhammad; Ahmed, Ashfaq (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the cause of hypochromic microcytic anemia in children presenting to Pediatric Outpatient Department (OPD). Study Design: Descriptive cross-sectional. Place and Duration of Study: Departments of Pathology and Pediatrics, Combined Military Hospital (CMH) Sargodha, from Jan to Jul 2022. Methodology: All patients having hypochromic microcytic anemia, aged between 6 months to 12 years of age, and fulfilling inclusion and exclusion criteria, were included in the study. Diagnosis and grading of anemia were done according to World Health Organization (WHO) criteria. Detailed clinical history, examination, and a panel of investigations, including hematological indices and parameters, biochemical, and immunological investigations, were done for evaluation. Results: A total of 359 children with hypochromic microcytic anemia were evaluated. The mean age of children was 2.95±2.40 years with male to female ratio of 1.6:1. In terms of severity, 3(3.03%) children had mild anemia, 38(38.38%) had moderate anemia and 58(58.58%) had severe anemia. Iron deficiency was found in 205(57.10%) children, followed by mixed deficiency in 91(25.30%), β-Thalassemia trait in 42(11.70%), and normal chemical and immunological profile in 21(5.80%) children. One case, each, of hereditary spherocytosis and lymphoblastic leukemia, was diagnosed on the basis of peripheral film. Conclusion: Nutritional deficiency was the most common etiology of hypochromic microcytic anemia followed by the β-Thalassemia trait; thus, chronic disease should be kept in mind while investigating refractory cases.